The Role of Information Technology in the Accounting Revolution - Nyoman Ayu Dian LESTARI; Ni Putu Dewi Krisna CAHAYA; Ni Made Raissa Meilin FERLINDA; Maria Nizia Pereira MONTEIRO; Maria Chetrine PUTRIANI (PT. Keberlanjutan Strategis Indonesia, 2024)
Purpose:The development of information technology has brought significant changes in the world of accounting. Digitalization of accounting processes through the use of computer hardware and software allows financial data processing to be faster, more precise, and more accurate. Information technology-based accounting information systems not only improve the efficiency and quality of financial reports but also strengthen strategic decision-making in organizations.Methodology:This study uses a literature review method to analyze the role of information technology in the accounting revolution. This method was chosen because the focus of the study is to explore and synthesize various existing findings and theories regarding the influence of information technology on accounting practices and the transformation of the accounting profession in the digital era.Findings:Technological advances open up new opportunities for the accounting profession, such as computer-based audits and information systems consulting. However, these changes also require increased capacity and competence of human resources to be able to adapt to rapid technological developments.Implication:Thus, the role of information technology becomes very vital in driving the accounting revolution towards more modern, effective and adaptive practices to the challenges of the digital era.